2002
DOI: 10.1002/ana.10304
|View full text |Cite
|
Sign up to set email alerts
|

Instability of a premutation allele in homozygous patients with myotonic dystrophy type 1

Abstract: Myotonic dystrophy type 1 (DM1) is caused by the expansion of an unstable CTG repeat in the DMPK gene on chromosome 19q13.3. We present two siblings with DM1 who each inherited a premutation allele, (CTG)43, stably transmitted from the mother and a full-mutation allele, either (CTG)500 or (CTG)180, derived from a paternal protomutation allele, (CTG)52. Small-pool polymerase chain reaction analysis showed that the (CTG)52 repeat allele was relatively stable in somatic tissues but was highly unstable in the male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 20 publications
0
17
0
Order By: Relevance
“…As seen in HD, intermediate alleles of these trinucleotide disorders do not confer the disease phenotype, but due to the possibility of repeat expansion, there is a risk of disease in offspring. Furthermore, numerous factors, similar to HD, have been identified that influence the likelihood of repeat instability for these trinucleotide disorders (45,46,(68)(69)(70)(71)(72)(73). Analogous to HD, these trinucleotide disorders also lack precise quantified risk estimates for affected offspring that account for factors influencing instability.…”
Section: Discussionmentioning
confidence: 99%
“…As seen in HD, intermediate alleles of these trinucleotide disorders do not confer the disease phenotype, but due to the possibility of repeat expansion, there is a risk of disease in offspring. Furthermore, numerous factors, similar to HD, have been identified that influence the likelihood of repeat instability for these trinucleotide disorders (45,46,(68)(69)(70)(71)(72)(73). Analogous to HD, these trinucleotide disorders also lack precise quantified risk estimates for affected offspring that account for factors influencing instability.…”
Section: Discussionmentioning
confidence: 99%
“…All reports concerning the correlation between CTG- repeat and disease severity were based on the analysis of CTG repeats expansion in each patient's leukocyte rather than in cardiomyocytes. We should focus on CTG repeats in cardiomyocytes when we make an attempt to investigate about the correlation between cardiac involvement and the CTG repeats expansion, as it was recently reported that somatic instability is often seen in patients of DM1 (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…The DM1 predisposing mutation seems to have originated only once for both the disease-causing alleles and the protomutated state were found to be in tight association with the same set of surrounding markers, suggesting a single common ancestral chromosome (Abbruzzese et al 2002;Brunner et al 1989;Goldman et al 1995Goldman et al , 1996Junghans et al 2001;Yamaoka et al 1990). Due to its single origin, the ancestral haplotype represents a genetic signature of DM1 or its protomutated alleles.…”
Section: Introductionmentioning
confidence: 99%